Navigating the quandaries of asylum storytelling in Dina Nayeri’s Who Gets Believed? - Kumar, Parveen; Gaurav, Kumar (Penerbit Universiti Kebangsaan Malaysia, 2025)
The current discourse on refugee justice poses a significant question: How do the asylum systems decide to dis/believe the stories of asylum seekers? At present, through a screening process, the asylum seekers are categorised as ‘deserving’ or ‘undeserving’, ‘rightful’ or ‘unrightful’, ‘refugees’ or ‘migrants’, and ‘victims’ or ‘threats’. This reductionist approach overlooks the intersection of contextual factors that complicate the experiences of displaced people. This paper identifies the bifurcated nature of asylum storytelling: first as a conduit for conveying personal experiences and second as a barrier to getting believed. Through an analysis of five asylum cases, approaching them as metaphors, genre, and discourse, depicted in Dina Nayeri’s book, Who Gets Believed?, the paper examines the vulnerabilities within the UK and US asylum systems that limit asylum seekers’ voice in storytelling. Based on a consolidated narrative inquiry and conceptual content analysis framework, the paper complicates the determinants of belief, credibility, and consistency in the institutional subculture of the asylum system, the ‘culture of disbelief’. The paper teases out the implications of the instinctive response of the asylum-granting authorities towards asylum storytelling as an illustration of the politics of believability materialising as a loss of truth, language, meaning, and narrative for the storyteller in the asylum space. Additionally, it highlights the role of new refugee literature in problematising the quiet politics of storytelling and envisioning solutions for centring asylum storytellers’ voices, experiential truth, and narrative.